PENGEMBANGAN VIDEO ANIMASI BERBASIS ANIMAKER PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SDN BANJARSARI 2 KOTA SERANG - Anggun Mardhina Ningtyas; Ratna Sari Dewi; M Taufik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Media is something that cannot be separated from a learning process. Variations in the use of media are necessary to make students motivated to learn. This research aimed to produce a product of animaker-based animation video. The type of this research was Research and Development (R&D) using the Borg and Gall model which had been modified by Sugiyono. This model consisted of six stages: potential and problem analysis, data collection, product design, product design validation, product revision, and product testing. The subjects of this study were 39 grade IV students of SDN Banjarsari 2 Serang. This product was tested to 20 students in a limited trial. Based on the results of data analysis, it was found that 1) the percentage of the average score from expert validation was 84.7% which was included in